Method of Reconstruction of Language Spatial Picture of the World according to Written Monuments of Pre-National Period (on Example of “Arable Land” Field) - L. A. Inyutina; T. S. Shilnikova (Научный диалог)
The work is devoted to the problem of reconstruction of the language spatial picture of the world in diachrony. The relevance of the study is due to the discrepancy between the modern linguistic consciousness and the mentality of native speakers, who created texts 4 centuries ago, attracted as a research material. The scientific novelty of the work lies in the expansion of the source base of cognitive and semantic research through Siberian monuments of business writing of the 17th century, not previously studied. The novelty of the work is also the development of a method of reconstruction of a semantic field based on the analysis of such texts. The aspects of the study (cognitive, semasiological, territorial, diachronic) are substantiated. Its methodological base (principles of historical and cultural, structural-system and conceptual analysis of lexical material) is determined. The concept of semantic field, representation of its features, boundaries, boundaries of its core and periphery is specified. The article describes the method of reconstruction of the semantic field of space according to the monuments of Siberian business writing of the 17th century on the example of the field “Arable Land.” The sequence of techniques of cognitive-semantic analysis of lexical units in the monuments of writing is characterized, which allows to identify semantic paradigms that form the core and periphery of the semantic field, to present its structure as a hierarchy of semantic paradigms. The conclusion is substantiated that the reconstruction of the semantic field of space allows to reveal the essential properties of the regional spatial picture of the world.